Developing Massive Open Online Course (MOOC) : Need Analysis of Teaching Materials for Madrasah English Teachers - Dewi Wahyu Mustikasari (Register Journal, 2017)
The purposes of this study are (1) to recognize the textbooks or other teaching materials used by the Madrasah English teachers, (2) to identify their obstacles in preparing the teaching materials, (3) to analyze the teaching materials which can be developed in MOOC, (4) to analyze the teaching materials for MOOC which are related to the Indonesian curriculum, (5) to analyze their willingness of proffesional teaching development by joining MOOC. This study used a descriptive qualitative approach. Moreover, the subjects of the study were 3 English teachers of MTs Negeri Salatiga and 5 English teachers of MAN Salatiga. Observation, interview and documentation were used as the techniques of data collection. The results showed that (1) they used the textbooks from Ministry of Education (MOE), selected main handbooks, supplemenatary teaching materials from certain websites, (2) communicative competence as the main issue of content of textbook from MOE gave different challanges for them to prepare the teaching materials, (3) authentic materials were highly needed to be developed in MOOC, (4) characters building based-teaching materials needed to be developed too as those are the uniqueness of the Indonesian curriculum, (5) they had less interest to join MOOC as their way to develop their proffesional teaching development.Keywords: MOOC, English teaching materials, authentic materials, characters building